Renovation of an Academic Building’s Envelope, Lighting, and Air Conditioning System According to Thailand Building Energy Code for Energy Consumption Reduction - Pathomthat Chiradeja; Surakit Thongsuk; Santipont Ananwattanaporn; Atthapol Ngaopitakkul (Sustainability, 2023)
This study evaluated the feasibility of building renovation with regard to the aspects of economy and energy. An academic building located in Bangkok, Thailand was selected for a case study. Four sub-systems, namely, the building envelope, lighting system, air conditioning unit, and electrical system, were renovated. From the energy perspective, Thailand’s Building Energy Code was used as an evaluating standard, and the BEC software (Version 2.6.0) was employed for the calculations. The economic feasibility of the renovation was determined on the basis of the internal rate of return and discounted payback period. It was demonstrated that the renovation can result in a reduction in the annual energy consumption of the entire building by up to 55.44%. In regards to economic feasibility, the renovation project can achieve a payback period of 4.98 years with 20.89% IRR. In addition, the renovation of a building can lead to spare capacity of the transformer for electric vehicle charger loads. Thus, the renovation of an old building into an energy-efficient building in compliance with building code can afford benefits both in terms of electricity consumption reduction and decreased energy cost for the project owner and provide opportunity for the building to support future load.
Keywords: Building Energy and Comfort Optimization; Energy Efficiency and Management; Smart Grid Energy Management